Impact of COVID-19 on Continuing Medical Education—Results of an Online Survey Among Users of a Non-profit Multi-Specialty Live Online Education Platform - Schulte, Tobias L.; Gröning, Thilo; Ramsauer, Babett; Weimann, Jörg; Pin, Martin; Jerusalem, Karen; Ridwan, Sami (Frontiers in Medicine, 2021)
Background: The Coronavirus Disease-2019 (COVID-19) pandemic accelerated digitalization in medical education. Continuing medical education (CME) as a substantial component of this system was relevantly affected. Here, we present the results of an online survey highlighting the impact on and the role of online CME. Methods: An online survey of 44 questions was completed by users of a German online CME platform receiving an invitation via newsletter. CME habits, requirements, personal perception, and impact of the pandemic were inquired. Standard statistical methods were applied. Results: A total of 2,961 responders took the survey with 2,949 completed surveys included in the final analysis. Most contributions originated from Germany, Austria, and Switzerland. Physicians accounted for 78.3% (57.5% hospital doctors) of responses followed by midwives (7.3%) and paramedics (5.7%). Participating physicians were mainly board-certified specialists (69%; 55.75% hospital specialists, 13.25% specialists in private practice). Frequent online lectures at regular intervals (77.8%) and combined face-to-face and online CME (55.9%) were favored. A duration of 1–2 h was found ideal (57.5%). Technical issues were less a major concern since the pandemic. Conclusion: A shift from face-to-face toward online CME events was expectedly detected since the outbreak. Online CME was accelerated and promoted by the pandemic. According to the perception of users, the CME system appears to have reacted adequately to meet their demand but does not replace human interaction.